2006
DOI: 10.1007/s00213-006-0493-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging and electrophysiological studies of the effects of acute tryptophan depletion: a systematic review of the literature

Abstract: The combination of ATD with modern brain imaging techniques allows the investigation of the neurophysiological effects of reduced 5-HT synthesis on global brain activity, executive functions, memory, attention, and affect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 76 publications
6
46
0
Order By: Relevance
“…This view would be consistent with a recent meta-analysis by Fusar-Poli et al (2006), in which acute trytophan depletion was found to modulate cortical activity in areas that are Langenecker et al (2005). The authors reported executive impairments and deficits in the perception of emotional faces that were unrelated in depressed patients.…”
Section: Major Depression and Prosody Comprehension 557supporting
confidence: 88%
“…This view would be consistent with a recent meta-analysis by Fusar-Poli et al (2006), in which acute trytophan depletion was found to modulate cortical activity in areas that are Langenecker et al (2005). The authors reported executive impairments and deficits in the perception of emotional faces that were unrelated in depressed patients.…”
Section: Major Depression and Prosody Comprehension 557supporting
confidence: 88%
“…ATD lowered the plasma TRP/LNAA by 77%, which is comparable with previous studies using the same CP ATD method (Evers et al 2005) or the classic ATD mixture (Van der Does 2001). Previous studies using the classic ATD mixture have reported an increase in plasma TRP of up to 200% in the balanced (TRP+) condition (for a review see Fusar-Poli et al 2006), whereas the CP ATD method has been found to be more effective in maintaining a stable TRP+ condition (Evers et al 2005;Firk and Markus 2008). In the present study, the TRP/LNAA ratio also increased by 62% in the TRP+ condition suggesting that the TRP+ condition may also be psychoactive due to an increase in 5-HT synthesis.…”
Section: Discussionsupporting
confidence: 45%
“…One accepted method to study behavioral and cognitive effects of transiently reduced 5-HT availability in humans is the acute tryptophan depletion (ATD) strategy (for a review see Fusar-Poli et al 2006;Young et al 1985). In this procedure, brain 5-HT is reduced through depletion of plasma tryptophan (TRP, a precursor of 5-HT) availability for uptake into the brain by intake of a TRP-free amino acid mixture that contains all of the essential amino acids except for TRP.…”
Section: Introductionmentioning
confidence: 99%
“…We retrieved additional references identified in previous reviews 11,12,[18][19][20][23][24][25] and cross-references from identified studies. Two reviewers (HGR and NSM) independently selected articles based on the a priori inclusion and exclusion criteria as stated above.…”
Section: Literature Searches and Selectionmentioning
confidence: 99%